Dichlorodioxomolybdenum(VI) Complexes: Useful and Readily Available Catalysts in Organic Synthesis - Hernández-Ruiz, Raquel; Sanz, Roberto (Synthesis, 2018)
Molybdenum(VI) dichloride dioxide (MoO2Cl2), and its addition complexes [MoO2Cl2(L)n; L = neutral ligand], are commercially or easily available and inexpensive transition-metal complexes based on a non-noble metal that can be applied as catalysts for various organic transformations. This short review aims to present the most significant breakthroughs in this field.1 Introduction2 Preparation and Reactivity of MoO2Cl2(L)n Complexes2.1 Synthesis and Structure2.2 Reactivity of Dichlorodioxomolybdenum(VI) Complexes3 Redox Processes Catalyzed by MoO2Cl2(L)n Complexes3.1 Deoxygenation Reactions Using Phosphorus Compounds3.2 Deoxygenation and Hydrosilylation Reactions Using Silanes3.3 Reduction Reactions Using Hydrogen3.4 Deoxygenation Reactions with Boranes and Thiols3.5 Reduction Reactions with Glycols3.6 Oxidation Reactions4 Ambiphilic Reactivity of MoO2Cl24.1 Amphoteric Lewis Acid–Lewis Base Catalyzed Reactions4.2 Lewis Acid Type Catalyzed Reactions5 Conclusion and Perspective
Keywords: dioxomolybdenum(VI) complexes; reduction; oxidation; deoxygenation; Lewis acid; nitroaromatics; sulfoxides